The effect of icepack cooling on skin and muscle temperature at rest and after exercise - Mars, M; Hadebe, B; Tufts, M (South African Journal of Sports Medicine, 2006)
Objective. To compare cooling of skin, subcutaneous fat and muscle, produced by an icepack, at rest and after short-duration exhaustive exercise. Methods. Eight male subjects were studied. With the subject supine, hypodermic needle-tip thermistors were inserted into the subcutaneous fat and the mid-portion of the left rectus femoris, to a depth of 1 cm plus the adipose thickness at the site, and a temperature probe was placed on the skin overlying the needle tips. A pack of crushed ice was applied for 15 minutes and temperatures were recorded before, during, and for 45 minutes after icepack application. Thereafter, subjects underwent a ramped, treadmill, VO2max test, an icepack was applied after temperature probes were inserted into the right leg and measurements were made as before. Results. After the treadmill run, skin (Sk), subcutaneous (SC) and muscle (Ms) temperatures (mean ± standard deviation (SD)) were 0.9 ± 1.3, 1.0 ± 0.7 and 1.3 ± 0.8°C higher than at rest. After 15 minutes of icepack cooling, temperatures fell in the exercised limb by 22.7 ± 1.5°C (Sk), 13.5 ± 4.2°C (SC) and 9.3 ± 5.5°C (Ms) and in the control limb by 20.7 ± 2.9°C (Sk), 11.4 ± 2.0°C (SC) and 8.7 ± 2.6°C (Ms). The reductions in temperature were significant in both the control and exercised limbs. Forty-five minutes after icepack cooling, muscle temperature was still approximately 5°C lower in both the rested and exercised muscle (p < 0.001). Individual variations in response to cooling were noted. Conclusions. Cooling of superficial muscle occurs after high-intensity exercise. The degree of cooling is not uniform. This may be due to differences in the sympathetic response to cooling, influencing haemodynamic and thermoregulatory changes after exercise. This needs further investigation. South African Journal of Sports Medicine Vol. 18 (3) 2006: pp. 60-66